2021
DOI: 10.1186/s12913-021-06861-y
|View full text |Cite
|
Sign up to set email alerts
|

Professionals’ responses to the introduction of AI innovations in radiology and their implications for future adoption: a qualitative study

Abstract: Background Artificial Intelligence (AI) innovations in radiology offer a potential solution to the increasing demand for imaging tests and the ongoing workforce crisis. Crucial to their adoption is the involvement of different professional groups, namely radiologists and radiographers, who work interdependently but whose perceptions and responses towards AI may differ. We aim to explore the knowledge, awareness and attitudes towards AI amongst professional groups in radiology, and to analyse th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 28 publications
2
63
0
Order By: Relevance
“…The support rate for the statement that AI could replace human physicians ranged from 6 to 78% ( 19 , 37 , 58 ), of which 31 (77.50%) studies showed that the support rate was less than half ( 11 , 16 19 , 21 , 22 , 24 , 25 , 30 , 33 37 , 39 42 , 44 50 , 55 , 56 , 59 , 60 , 63 ). Radiologists did not view AI as a threat to their professional roles or their autonomy, however, radiographers showed greater concern about AI undermining their job security ( 68 ). In our questionnaire, most disagreed that physicians will be replaced by AI in the future (68% disagreed).…”
Section: Resultsmentioning
confidence: 99%
“…The support rate for the statement that AI could replace human physicians ranged from 6 to 78% ( 19 , 37 , 58 ), of which 31 (77.50%) studies showed that the support rate was less than half ( 11 , 16 19 , 21 , 22 , 24 , 25 , 30 , 33 37 , 39 42 , 44 50 , 55 , 56 , 59 , 60 , 63 ). Radiologists did not view AI as a threat to their professional roles or their autonomy, however, radiographers showed greater concern about AI undermining their job security ( 68 ). In our questionnaire, most disagreed that physicians will be replaced by AI in the future (68% disagreed).…”
Section: Resultsmentioning
confidence: 99%
“…While research related to radiologists' roles, clinical practise, and education in relation to AI has flourished, as discussed in the abovementioned paragraphs, very little research has considered the impact of AI on radiographers and their perception of using it in clinical practise. The limited literature available would suggest that radiographers are keen to engage with AI but controversy still exists whereby some radiographers feel that AI may deplete or threaten their jobs in the future whilst others think it may lead to more advanced role developments (31)(32)(33)(34). Abuzaid et al (35) surveyed the opinions of 34 radiologists and 119 radiographers in the UAE on their willingness to accept AI into practise.…”
Section: The Impact Of Ai On Radiographersmentioning
confidence: 99%
“…It is therefore important to recognize that not all clinical tasks require or may benefit from the use of radiomics. In this regard, recent studies have reported on the knowledge and attitude of radiologists towards the clinical adoption of AI [56][57][58]. A survey of over 1000 radiologists revealed that a majority (77%) of participants had a positive attitude and were favorable towards the adoption of AI.…”
Section: Discussionmentioning
confidence: 99%
“…The perceived benefits of applying AI to routine radiologic practice reported by the participants included lower diagnostic error rates (73% of respondents) and optimization of radiologist workload (68% of respondents) while the risk of diminished professional reputation and increased costs, the higher workload for AI system maintenance and data analysis (39% of respondents) were the main concerns [56]. Similarly, a qualitative study by Chen et al observed that radiologists believe that AI has the potential to assist in performing repetitive tasks which in turn could allow them to focus on challenging clinical scenarios or reads [57]. The study also showed that the awareness and knowledge about AI greatly varied among professionals in radiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation